PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN LARUTAN CAP KAKI TIGA DI KOTA PALEMBANG - Gunawan Gunawan; Irwan Septayuda (STIE Wiyatamandala, 2023)
The purpose of this study was to determine the effect of brand image on the decision of Cap Kaki Tiga solution in Palembang city, to determine the effect of product quality on purchasing decisions of Cap Kaki Tiga solution in Palembang city. To determine the effect of promotion on the purchase decision of Cap Kaki Tiga solution in Palembang city, to determine the effect of brand image, product quality and promotion on the purchase decision of Cap Kaki Tiga solution in Palembang city. This study uses a quantitative data method, namely where the data used in this study analyzes whether there is an influence between brand image, product quality and promotion variables on the purchasing decision of the three-foot cap solution in the city of Palembang. This study uses multiple linear analysis methods using a computer program, namely the software package for the social sciences (SPSS). The results of this study are Brand Image, Product Quality and Promotion Simultaneously (Simultaneously) significantly influence the decision to buy a three-foot cap solution in the city of Palembang.